Using linked records to improve National estimates of hospital admissions for coronary heart disease (CHD). (2017) - Lopez, Derrick; Nedkoff, Lee; Hobbs, Michael; Briffa, Tom; Preen, David; Heyworth, Jane; Sanfilippo, Frank
No abstract available